Expression of matrix metalloproteinase-1 in knee osteoarthritis: Association with disease severity - Honsawek, Sittisak; Poonphakdi, Jariya; Deepaisarnsakul, Benjamad; Tanavalee, Aree; Yuktanandana, Pongsak; Ngarmukos, Srihatach; Tantavisut, Saran (Chulalongkorn Medical Journal, 2023)
Background : Osteoarthritis (OA) is characterized by the progressive loss of articular cartilage and osteophyte formation resulting in pain, stiffness, reduced motion, swelling, crepitus, and disability. The aim of this study is to investigate plasma and synovial fluid matrix metalloproteinase-1 (MMP-1) levels of patients with primary knee OA and to examine their relationship with disease severity. Methods : Thirty-two patients aged 53 - 83 years old with knee OA and 10 healthy individuals were recruited into this study. Disease severity was determined using weight-bearing anteroposterior radiographs of the affected knee. The radiological grading of knee OA was performed according to Kellgren- Lawrence grading system. MMP-1 levels in both plasma and synovial fluid were evaluated using enzyme-linked immunosorbent assay. Results : The mean plasma MMP-1 levels were higher in OA patients compared to controls; however, the difference was not statistically significant (198.0 ± 63.5 vs. 94.2 ± 2.4 pg/ml, P = 0.1). MMP-1 levels in synovial fluid of OA patients (2632.8 ± 525.2 pg/ml) were 13-fold higher than in corresponding blood samples (P <0.001), and were 26-fold higher than in the plasma of healthy controls (P <0.001). Subsequent analysis revealed that synovial fluid MMP-1 levels of knee OA patients were positively correlated with OA grading (r = 0.873, P< 0.001). Conclusions : MMP-1 levels in synovial fluid are positively associated with the severity of joint damage in knee OA. Synovial fluid MMP-1 may serve as a biomarker for determining disease severity and could play a possible role in the pathogenesis of osteoarthritis.